Stephen Chan (2021) - African Political Thought : An Intellectual History of the Quest for Freedom - Aubry, Ayrton (Revue d'histoire contemporaine de l'Afrique, 2023)
Recensé : Stephen Chan, African Political Thought : An Intellectual History of the Quest for Freedom, Londres, Hurst Publishers, 2021, 240 p.